Unjust Seizure : Conflict, Interest, and Authority in an Early Medieval Society - Brown, Warren, 1963- (Book collections on Project MUSE., 2001)
"Most scholarship in English on the political and social order of early medieval Europe deals with the Western Frankish regions. Warren Brown shifts the focus to the East, concentrating on conflicts and their resolutions to learn how a central authority could affect local societies in the Middle Ages." "By drawing on the recent work of anthropologists and political scientists on topics such as dispute resolution and the dynamics of conquest and colonization. Brown considers issues larger than the procedures for handling conflict in the early Middle Ages: How could a ruler exercise power without the coercive resources available to the modern state? In what ways can a people respond to military conquest?"--Jacket.